Penyelesaian Sengketa Tanah Ulayat antara Masyarakat Kampung Kaptiau dan Kampung Mawesday di Kabupaten Sarmi - Palenewen, James Yoseph (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research aims to determine the factors that give rise to customary land disputes between the people of Kaptiau village and Mawesday village, and also to find out the form of resolution of customary land disputes through customary law among the people of Kaptiau village and Mawesday village. The approach method used in this research is a normative and empirical juridical approach, namely an approach that refers to laws, library materials, written regulations or other secondary legal materials, and to see how they are implemented through field research. or the reality that occurs at the research location. The results of this research reveal that the dispute that occurred between the people of Kaptiau village and Mawesday village began when a timber company wanted to build an oil tank in Kaptiau village, but the residents of Mawesday village claimed that the land to be built was still part of the community's customary rights. Mawesday village does not belong to Kaptiau village, so there were road blockades and clashes between the two villages, resulting in injuries caused by sharp weapons to residents of both villages. In resolving the customary land dispute between Kaptiau village and Mawesday village which has led to clashes and resulted in residents being injured due to sharp weapons from the two villages, the authorities (police) act as mediators or third parties whose job is only to assist the disputing parties in resolving the problem and did not have the authority to make decisions, with the presence of the tribal heads of the two villages to help resolve the problems that occurred regarding customary land.